Herbert Hoover and the Organization of the American Relief Effort in Poland (1919-1923) - Matthew Lloyd Adams (European Journal of American Studies)
Poland, recreated after the armistice of 1918, was confronted at its rebirth with four very severe challenges: welding together the separate sections of the dissected country, which for many decades had been under the rule of Prussia-Germany, Austria and Russia; creating a functioning administration and military force for the country; ensuring the recovery of agriculture, which, during World War I, had seriously declined; and restarting industries destroyed or closed during foreign military occupation. Even under the valuable leadership of the first Prime Minister of the new Polish Republic Ignacy Paderewski and Marshal Jozef Pilsudski, the Poles could not accomplish the goal of rebuilding a strong Poland without outside help. The American Relief Administration (ARA), founded and led by Herbert Hoover, offered their help. The ARA, with its food aid and provision of economic assistance and expertise, played an important role in bringing about stability in the newly independent state of Poland. This paper examines the many steps Herbert Hoover had to take to arrange food relief in Poland and will outline the organization of the ARA, including the establishment of the Polish relief organization and the introduction of young Polish-American women, called the Grey Samaritans, into the field.